PENGARUH RETURN ON ASSETS, DEBT TO EQUITY RATIO, PRICE EARNING RATIO DAN FIRM-SIZE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KATEGORI INDEKS LQ-45 DI BURSA EFEK INDONESIA - Triana Zuhrotun Aulia (Balance Vocation Accounting Journal, 2017)
Price to Book Value (PBV) is the ratio of the market value of equity to the book value of equity. PBV is the level of ability to create a company's value relative to the amount of capital invested. This study will analyze both simultaneous and partial effect of return on assets, debt to equity ratio, price earning ratio and firm-size to price book value. Companies classified in LQ-45 selected as the population used in this study are listed on the Stock Exchange 2012-2016 period. Purposive sampling is used to get the sample in this research using criterias and 18 companies or 72 firm-years are the samples. Analysis tool in this research using spss 23.0. This research is using multiple linear regression. Based on the results of the partial test (t test) on the real level (α) = 5% can be seen that the variabel return on assets, debt to equity ratio and price earning ratio have a significant and positive impact on price book value, meanwhile firm-size have no significant effect on price book value. Keywords :   Firm value, Price Book Value, Return on Asset, Debt to Equity Ratio, Price Earning Ratio, Firm-size.